TRANSFORMASI FOKALISASI DALAM EKRANISASI NOVEL “MENGAKU BAPAK” KE FILM FATHER AND SON - Diana Lase; Irma Suryani; Dwi Rahariyoso (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by changes in the representation of character perspective in the process of novel-to-film adaptation. The study aims to describe the forms of focalization in the novel Mengaku Bapak and the film Father and Son, examine the representation of focalization in both media, and identify the forms of focalization transformation occurring in the adaptation process. This research employs a qualitative descriptive method using narratological and adaptation approaches. The data consist of narrative excerpts from the novel and dialogues from the film that reflect the perspective of the main character. Data were analyzed using Genette’s theory of focalization and Eneste’s theory of adaptation. The findings reveal that both Mengaku Bapak and Father and Son are dominated by fixed internal focalization, with Iman functioning as the central focalizer. Major events in both works are presented through Iman’s subjective experiences. Although the type of focalization remains unchanged, the adaptation process transforms the way those subjective experiences are represented. In the novel, the character’s inner experiences are conveyed explicitly through narration that provides direct access to his thoughts and feelings, whereas in the film the same experiences are represented through dialogue and actions. The dominant forms of transformation identified are variation and reduction. Therefore, the adaptation process does not alter the type of focalization employed but rather transforms the mechanism through which the character’s subjective experiences are represented in accordance with the characteristics of each medium.